Caffeic acid phenethyl ester attenuates dextran sulfate sodium-induced ulcerative colitis through modulation of NF-κB and cell adhesion molecules - Pandurangan, Ashok Kumar; Mohebali, Nooshin; Hasanpourghadi, Mohadeseh; Mohd Esa, Norhaizan (Springer Nature, 2022)
Ulcerative colitis (UC) is a serious health condition and defined as inflammation in the colon. Untreated, UC can develop into colitis-associated cancer (CAC), for which effective medicines are not available. Natural products are a better choice to treat UC by alleviating the inflammation. Caffeic acid phenethyl ester (CAPE) is a phenolic compound and known for its beneficial effects, including antibacterial, anti-inflammatory, anti-diabetic, and anticancer. We aimed to study the effect of CAPE on dextran sulfate sodium (DSS)-induced UC in mouse model. Administration of CAPE to DSS-induced mice protected against colon damage by improving body weight of mice, reducing the weight of spleen, and increased colon length. In addition, administration of CAPE resulted reduced the activity of myeloperoxidase (MPO) and CD68+ positive cells. Furthermore, a significant decrease in the production of key cytokines and the expression of nuclear factor (p65-NF)-κB. Moreover, p65-NF-κB activation was reduced in lipopolysaccharide (LPS)-treated RAW 264.7 macrophage cells from mouse origin. CAPE treatment leads to the reduced expressions of intercellular adhesion molecules (ICAM)-1 and vascular cell adhesion molecules (VCAM), both are key cell adhesion molecules. The results of this study clearly indicate that CAPE can potentially control inflammation in the colon and can be used as a therapy for UC.